Family Influence on Student Mental Health and Academic Achievement in University Transition - Sampe, Prisca Diantra; Sari, Dewi Puspita; Makulua, Izak Jakobis (Guidance and Counseling Study Program, Pattimura University, 2024)
This study explores the crucial role of social support in facilitating the transition of adolescents from high school to university, focusing on two respondents, BM and MM. BM, in his second semester at a state university, struggles with the challenges of living independently in a boarding house, feeling significant emotional strain due to limited parental communication. MM, a student at a private university, maintains a close and supportive relationship with his father, despite the absence of his mother since he was two years old. The research highlights the importance of different types of social support—appraisal, belonging, and tangible—in aiding students' adaptation to university life. Appraisal support involves the availability of someone to discuss problems, while belonging support encompasses emotional and task-related assistance from family members. Tangible support refers to material assistance provided by parents. The findings indicate that effective social support, particularly from family, is essential for promoting mental health, academic success, and overall well-being during this critical transition period. The study underscores the need for future research to explore these dynamics further, considering broader cultural and socio-economic contexts that influence the availability and effectiveness of social support.